MON-440 Unusual Case of Metastatic Struma Ovarii Diagnosed at the Time of Hysterectomy - Merrill, Jennifer (J Endocr Soc, 2020)
Introduction: Struma ovarii is rare ovarian teratoma composed of more than 50% mature thyroid tissue, which can rarely transform to malignancy. There are fewer than 200 cases reported and no established treatment approach. We present a case of metastatic malignant struma ovarii. Case Presentation: A 41 year old female was diagnosed with metastatic papillary thyroid carcinoma (PTC) after it was found on uterine histopathology. History was notable for remote left ovarian cystectomy of a mature teratoma with prominent thyroid component. She had no personal or family history of craniocervical radiation or thyroid cancer. Eight years later, she had a total hysterectomy for menorrhagia. Pathology showed subcentimeter serosal deposits of follicular variant PTC, staining positive for thyroglobulin, CK19, and HBME1. Endometrial and cervical pathology were normal; the myometrium had many leiomyomata. Post-hysterectomy TSH was 2.3 (0.34 - 5.66 µIU/mL), and thyroglobulin 44.3 (<=33.0 ng/mL). Thyroid ultrasound showed a 7 mm isoechoic nodule without lymphadenopathy. Whole body PET/CT showed multiple hypermetabolic masses in the pelvic peritoneum and liver. The right ovary had many cystic lesions and was enlarged to 5.3 x 4.5 cm. She underwent partial hepatectomy, oophorectomy, salpingectomy, and omental resection with no residual disease. Pathology showed follicular variant PTC in both ovaries, peritoneum, colonic mesentery, and omentum. Thyroglobulin fell to 6.9 ng/mL 3 weeks later. A 0.2 cm focus of follicular variant PTC with capsular invasion was found on pathology after total thyroidectomy. She underwent radioiodine ablation with 150 mCi. Postablative scan showed residual activity in the thyroid bed and right hemipelvis, but no new foci of activity. CT abdomen showed resolution of perihepatic lesions and thyroglobulin declined further to 0.5 ng/mL. Discussion: A low risk of recurrence (7.5%) has been reported in patients with malignant struma ovarii, with survival rates of 96.7% at 5 years and 84.9% at 20 years, despite a variety of surgical and adjuvant management strategies. Unilateral cystectomy, unilateral salpingo-oophorectomy, or total abdominal hysterectomy and bilateral salpingo-oophorectomy may be sufficient for patients with well differentiated thyroid cancer arising in struma ovarii without metastases. Thyroid ultrasound should be performed to exclude primary thyroid malignancy. Patients with distant metastases may benefit from aggressive treatment including resection of gross abdominal and pelvic disease and total thyroidectomy to facilitate radioactive iodine ablation and surveillance for recurrence. Conclusion: Due to its rarity, there is no consensus on optimal treatment of malignant struma ovarii. More research in this field is warranted.